EFEKTIVITAS EKSTRAK ETANOL KULIT TERONG UNGU (Solanum melongena L.) SEBAGAI ANTIMALARIA TERHADAP JUMLAH BASOFIL DARAH MENCIT (Mus musculus) YANG DIINDUKSI Plasmodium berghei - Wahyuningsih, Aprilia Tri; Kahtan, Muhammad Ibnu; Widiyantoro, Ari (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Malaria is one of the disease which spreads through the bite of female Anopheles mosquito caused by Plasmodium parasite. Malaria can be treated with antimalarial drugs such as chloroquine and artemisin, but in some malaria-endemic areas, parasitic resistance to chloroquine has been reported so that malaria eradication becomes increasingly difficult. The occurrence of such resistance causes the need for new antimalarial findings. Eggplant (Solanum melongena L.) has many secondary metabolites, such as alkaloids, terpenoids, and flavonoids which have antiplasmodial activity. The aim of this research is to determine the effectivity of the ethanol extract of eggplant peels as an antimalarial to basophil in mice induced by Plasmodium berghei. Eggplant peel was extracted by maceration method using 70% ethanol. The analysis of secondary metabolites from the ethanol extract of eggplant peels used tube test and thin layer chromatography. The level of parasitemia and the number of basophil were calculated from blood smear of mice (Mus musculus) which were treated with extracts at a dose of 0.075 mg/20 g of body weight; 0.15 mg/20 of body weight; and 0.3 mg/20 g of body weight. 3.744 mg/20 g of body weight DHP was used as positive control and aquades was used as negative control. Research result show that ethanol extract of the eggplant peels contains groups of alkaloids, flavonoids, terpenoids, steroids, phenolic and saponins. 0.075 mg/20 g body weight of ethanol extract of the eggplant peels effectively reduces parasitemia. Ethanol extract of the eggplant peels in all dose groups did not have an effect on basophils. The conclusion of this research is ethanol extract of the eggplant peels has antimalarial activity and does not increase the number of basophils.